The Creative Economy as a Driver of Rural Development: A Case Study of Szigetköz in the Hungarian-Slovak Border Region in North-Western Hungary - Kézai, Petra Kinga; Gombos, Szandra (Eastern European Countryside, 2024)
Kevin Stolarick and Richard Florida (2006) argued that an agglomeration of those whose occupation is creative (or has a creative component) is responsible for regional innovation, using interaction and spillovers. Following this line of thought, this paper deals with the problem of cultural and creative industries (CCIs) in the Hungarian-Slovak cross-border area of Szigetköz, located in northwestern Hungary. In a strict sense, the aim is to explore the strengths and untapped potential of the region’s CCIs. The research methods adopted include statistical data analysis based on individual enterprises and firms and in-depth interviews (N=30). The study describes the micro-level CCI sector for the period 2015–2020, where the number of enterprises is steadily decreasing and the number of selfemployed is steadily increasing. However, most of the activities of the sector are less visible (and therefore less accessible) to the wider public. It also highlights the problems and gaps in the creative economy in the Szigetköz region, falling into four main categories: localisation of the creative economy, the ‘meeting points’ of supply and demand, cooperation and communication, and the operational and management issues of the creative economy.